First principles calculations to investigate structural, electronic, mechanical, thermoelectric and optical properties of Bi- and Se-doped SnTe. (May 2023) - Muthumari, M.; Manjula, M.; Veluswamy, Pandiyarasan; Kuznetsov, Denis V.
Abstract: Lead-based thermoelectric materials have a maximum figure of merit but are hazardous to humans and the environment. For this reason, we can replace tin-based lead-free materials and achieve the same figure of merit as lead-based thermoelectric materials. In this paper, we calculate the structural, electronic, mechanical, thermoelectric and optical properties of SnTe by co-doping it with Bi and Se using first principles calculation within the Generalized Gradient Approximation (GGA) through the Perdew-Burke-Ernzerhof(PBE) correlation scheme. Cohesive energies were calculated for each co-doping material and found to be maximum for Sn0.875 Bi0.125 Te0.875 Se0.125 . Computed elastic constants of all the cubic materials were obtained using the Thomas Charpin method integrated with the World of Interacting Electron and Nuclei due-2 Walter Kohn (WIEN2k) package. We found several mechanical properties of each material based on these constant values. We have observed an improvement in ductility and good stability for the Sn0.125 Bi0.875 Te0.125 Se0.875 material as confirmed by various mechanical properties. Boltzmann semi-classical approach as implemented in the BoltzTraP package with and without the calculation of spin-orbit coupling. Here the figure of merit is calculated without the contribution of phonons and SOC calculations were included with the ambient conditions. From the results, we achieve maximum power factor and ZT values using SOC and non-SOC calculations. We identified that the Sn0.875 Bi0.125 Te0.875 Se0.125 material shows a maximum ZT of 0.55, which is very much higher than the undoped SnTe and Sn0.125 Bi0.875 Te0.125 Se0.875 material shows a ZT of 0.49 using SOC calculations. The optical properties of each material were studied at ambient conditions and Sn0.875 Bi0.125 Te0.875 Se0.125 is consistent in the visible, IR and UV regions and it is adorable for IR detectors, solar cells and optoelectronic applications. Highlights: Co-doping SnTe with Bi and Se at five different concentrations to study structural and electronic properties. Mechanical properties of each material were studied using Thomas Charpin method, resulting in a material that was less hard and ductile. At 300 K, the maximum figure of merit (ZT) is achieved by SOC and non-SOC calculations. Each co-doping material's optical characteristics were investigated and found to be suitable for solar cell applications.